Changes taking place in the contemporary model of family policy in Poland – Analysis of the phenomena - Kacprowska, Krystyna (Eastern Review, 2021)
Family policy is a set of legal norms, actions and measures launched by the state to create appropriate living conditions for the family, its formation, proper functioning, and the fulfilment of all its important social roles. Transformation is an intentional process of changing one piece of the environment implemented over a period to create a new and primarily sustainable state of the environment. The author presents demographic data reflecting the process of the individualization of contemporary culture, which translates into changes in the contemporary family model. The main aim of the article is to present the changes taking place in the contemporary model of family policy in Poland and to analyze these phenomena.